The Importance of Parents as Modeling in The Formation of Children's Character - Rahmayanty, Dinny; Harahap, Nur Hasanah; Lestari, Ermida; Khofifah, Khairani; Saputra, Nurhadi (Faculty of Education Universitas Negeri Malang, 2024)
Family is the first and main forum that greatly influences the determination of a family's future. Overall, the family environment is a place and container for the growth and development of children (family members), where the family has a big factor in forming a child's soul and character, therefore it is necessary to create a positive environmental atmosphere by instilling the principles of moral values in life. a child in the family environment carried out by every family member, especially parents. Parents have a very important role in shaping a child's character. As the main role models in children's lives, parents can set good or bad examples in their daily behavior and attitudes. Therefore, it is important for parents to understand that they are the main models in forming children's character. In this article we will discuss the importance of parents as models in forming children's character